Privacy-preserving attribute-based encryption scheme on ideal lattices - Xixi YAN; Yuan LIU; Zichen LI; Yongli TANG; Qing YE (Tongxin xuebao)
Based on the small key size and high encryption efficiency on ideal lattices,a privacy-preserving attribute-based encryption scheme on ideal lattices was proposed,which could support flexible access policies and privacy protection for the users.In the scheme,a semi-hidden policy was introduced to protect the users’ privacy.Thus,the sensitive values of user’s attributes are hidden to prevent from revealing to any third parties.In addition,the extended Shamir secret-sharing schemes was used to construct the access tree structure which can support “and” “or” and “threshold” operations of attributes with a high flexibility.Besides,the scheme was proved to be secure against chosen plaintext attack under the standard mode.Compared to the existing related schemes,the scheme can yield significant performance benefits,especially the size of system public/secret keys,users’ secret key and ciphertext.It is more effective in the large scale distributed environment.